Tinjauan Pengetahuan Petugas Rekam Medis Dalam Peralihan Rekam Medis Manual Ke Rekam Medis Elektronik Di Puskesmas Kabupaten Tapin - Widya Wati, Ni wayan Kurnia; Apriyanti, Firda (HB PRESS, 2024)
Information and Communication Technology (ICT) systems have become an inseparable part in various aspects of life, including health services. Electronic Medical Records (RME) is a form of application of ICT in the health service system through computerization of patient data. RME development requires an assessment of the readiness to implement RME from the aspects of human resources, governance leadership, organizational culture and infrastructure. This study aimed to research is to determine the knowledge of medical records officers in transitioning manual medical records to electronic medical records at the Tapin Regency Health Center. The results of this study indicate that most of the medical record officers' knowledge is in transition manual medical records to electronic medical records mostly 17 people (60.7%) have sufficient knowledge. It would be better if the education of medical records officers at community health centers is well-educated behind the medical recorder so that they can carry out services in the medical records unit well and competently in their field because with appropriate education it will influence the officers' knowledge to be better and training is held to increase knowledge for medical record officers regarding the use of Electronic Medical Records (RME).